Pemahaman Orang Yang Berbahagia - Daniel Ari Wibowo (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2016)
There are many definitions for understanding the meaning of happiness. Every way is done by people to be able to get happiness in their lives. Many think that happiness is based solely on material problems. Is that right? Given that many are wallowing in wealth, but their lives are not happy. Then through Psalm 119: 1-3 this will be explained the meaning of happiness expected by God to happen to humans. Various problems may exist, but if you still hope and rely on God, then someone will be able to enjoy happiness in his life.